The Improvement of Skill Competence’s Sudents with Implementation of Learning Community Strategy Through Jigsaw Learning Model on Human Digestive System Materials Class VIII in SMPN 12 Padang - Vina Septiani; Syamsurizal Syamsurizal; Rahmawati Darussyamsu (Bioeducation Journal, 2017)
This research purpose to see the effect of applying the learning community strategy through Jigsaw to skill competency in human digestion system class VIII. This research was based on the problem in this school that in fact, learning by group has not run as expected. There are students less active in group activities and low willingness to share with frriends. This research is a experimental research with Non Randomized Control Group Posttest Only Design. The sample of this research choosed by used purposive sampling method. The result with tcalculate is 2,71 and ttable is 1,67 with α 0,05. It showed that tcalculate > ttable, so it concluded that learning community strategy through Jigsaw learning model can improvement the achievement of the skill competence of students.